Persepsi Guru SDN 09 Muaro Kalaban Terhadap Efektivitas Pelatihan Pengembangan Soal Numerasi Berbasis Aplikasi Testmoz - Iska, Yulike; Zaimil, Roza; Rosmiyati, Rosmiyati; Pratiwi, Reno Warni (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research is motivated by the importance of technology being integrated in learning, including numeracy. As a result of initial observations, 60% of students understood the basic concept of numeracy, while most teachers had no experience in developing numeracy problems or using the testmoz application. This study aims to describe the perception of SDN 09 Muaro Kalaban teachers on the effectiveness of training in the development of numerical questions based on the testmoz application. This study uses a quantitative descriptive approach with an instrument in the form of a questionnaire. The respondents in this study were 7 people. The data analysis technique used is descriptive analysis. The results of the study show that the majority of teachers have a very positive perception of this training. There were no negative responses from respondents to this training. The results of this study show that this training is effective in improving teacher competence, providing significant benefits to numeracy-based learning, and can be used as a model for teacher professional development in other schools. So it can be concluded that the training on the development of numeracy questions based on the testmoz application at SDN 09 Muaro Kalaban is considered very effective in improving teacher competence